Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445558
|View full text |Cite
|
Sign up to set email alerts
|

SoniBand: Understanding the Effects of Metaphorical Movement Sonifications on Body Perception and Physical Activity

Abstract: Negative body perceptions are a major predictor of physical inactivity, a serious health concern. Sensory feedback can be used to alter such body perceptions; movement sonification, in particular, has been suggested to affect body perception and levels of physical activity (PA) in inactive people. We investigated how metaphorical sounds impact body perception and PA. We report two qualitative studies centered on performing different strengthening/flexibility exercises using SoniBand, a wearable that augments m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
(170 reference statements)
1
6
0
Order By: Relevance
“…Second, the emotional processes triggered by the high frequency sounds, which made participants feel happier, as shown by the results, may have interacted with the bodily feelings, or both processes may have influenced each other. Our findings here relate to those from a previous qualitative study where bodily movement was paired with a sound rising in pitch similar to the musical sound we employed in Experiment 3; this study suggested that this sound could lead to more pleasantness and feelings of movement fluidity, body lightness and flexibility in the context of exertion 45 .…”
Section: Absolute Frequency Range and Bodily Movementsupporting
confidence: 83%
See 4 more Smart Citations
“…Second, the emotional processes triggered by the high frequency sounds, which made participants feel happier, as shown by the results, may have interacted with the bodily feelings, or both processes may have influenced each other. Our findings here relate to those from a previous qualitative study where bodily movement was paired with a sound rising in pitch similar to the musical sound we employed in Experiment 3; this study suggested that this sound could lead to more pleasantness and feelings of movement fluidity, body lightness and flexibility in the context of exertion 45 .…”
Section: Absolute Frequency Range and Bodily Movementsupporting
confidence: 83%
“…Further, note that the constant sound was included as a "control" or reference condition with which to compare the effect of the sounds changing in pitch (as in 13,37 ). This was preferred to a "no sound" condition, as it allowed controlling for the effect of simply listening to a sound (see other studies using similar control condition 28,45 ). Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations